2023
DOI: 10.3389/fonc.2023.1032364
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the ferroptosis-related STEAP3 gene is a specific predictor of poor triple-negative breast cancer patient outcomes

Abstract: ObjectiveThis study was designed to assess ferroptosis regulator gene (FRG) expression patterns in patients with TNBC based on data derived from The Cancer Genome Atlas (TCGA). Further, it was utilized to establish a TNBC FRG signature, after which the association between this signature and the tumor immune microenvironment (TIME) composition was assessed, and relevant prognostic factors were explored.MethodsThe TCGA database was used to obtain RNA expression datasets and clinical information about 190 TNBC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…CISD1-Dependent regulation of ferroptosis is shown in glutathione depletion–induced oxidative cardiomyopathy in murine hearts ( Li et al, 2024 ). CISD1 expression has been recently demonstrated as a ferroptosis hub gene of prognostic relevance for triple-negative breast cancer ( Yuan et al, 2023 ) and tumor immune filtration in gastric cancer ( Zang et al, 2023 ). NAF-1 (CISD2) is localized to the outer membrane of mitochondria, ER membrane, and mitochondrion-associated ER membranes.…”
Section: Protective Pathways and Novel Therapeutic Targets Against Fe...mentioning
confidence: 99%
“…CISD1-Dependent regulation of ferroptosis is shown in glutathione depletion–induced oxidative cardiomyopathy in murine hearts ( Li et al, 2024 ). CISD1 expression has been recently demonstrated as a ferroptosis hub gene of prognostic relevance for triple-negative breast cancer ( Yuan et al, 2023 ) and tumor immune filtration in gastric cancer ( Zang et al, 2023 ). NAF-1 (CISD2) is localized to the outer membrane of mitochondria, ER membrane, and mitochondrion-associated ER membranes.…”
Section: Protective Pathways and Novel Therapeutic Targets Against Fe...mentioning
confidence: 99%
“…However, the study was mainly based on the existing TCGA and GEO databases, and there is a lack of external data cohorts and experimental validation, which is necessary to improve the accuracy of the model. Yuan et al constructed the expression patterns of ferroptosis-related genes and found that 7 genes, such as CA9, CISD1, STEAP3, HMOX1, DUSP1, TAZ, and HBA1, were closely related to the overall survival (OS) of TNBC (37). In particular, STEAP3 showed high expression in TNBC tissues and cells.…”
Section: Ferroptosis In Tnbc Diagnosismentioning
confidence: 99%
“…The six-transmembrane epithelial antigen of prostate 3 (STEAP3) encodes a multipass membrane metalloreductase, which can participate in Fe 3+ transport as an iron transport protein [ 12 ]. Considering the close relationship between STEAP3 and cellular iron homeostasis, its role in a variety of cancers has been extensively studied [ 13 ]. A number of studies have found that upregulation of STEAP3 is strongly associated with poor prognosis in triple-negative breast cancer as well as gliomas, suggesting that STEAP3 may be used as a specific predictor [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the close relationship between STEAP3 and cellular iron homeostasis, its role in a variety of cancers has been extensively studied [ 13 ]. A number of studies have found that upregulation of STEAP3 is strongly associated with poor prognosis in triple-negative breast cancer as well as gliomas, suggesting that STEAP3 may be used as a specific predictor [ 13 , 14 ]. It has been also shown that STEAP3 expression is upregulated in renal cells and that it can affect the progression of renal cell carcinoma by regulating ferroptosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%